Factors associated with occupancy of pharmacist positions in public sector hospitals in Uganda: a cross-sectional study - Ocwa Obua, Thomas; Odoi Adome, Richard; Kutyabami, Paul; Kitutu, Freddy Eric; Fadhiru Kamba, Pakoyo (Human resources for health, 2017)
Pharmacists are invaluable resources in health care. Their expertise in pharmacotherapy and medicine management both ensures that medicines of appropriate quality are available in health facilities at the right cost and are used appropriately. Unfortunately, some countries like Uganda have shortage of pharmacists in public health facilities, the dominant providers of care. This study investigated the factors that affect the occupancy of pharmacist positions in Uganda’s public hospitals, including hiring patterns and job attraction and retention. Methods: A cross-sectional survey of 91 registered pharmacists practicing in Uganda and desk review of records from the country’s health care worker (HCW) recruiting agency was done in the months of May, June, and July, 2016. Pharmacist interviews were done using self-administered structured questionnaire and analyzed by descriptive statistics and chi-square test. Results: Slight majority (53%) of the interviewed pharmacists work in two sectors. About 60% of the pharmacists had ever applied for public hospital jobs. Of those who received offers (N=46), 30% had declined them. Among those who accepted the offers (N=41), 41% had already quit. Meanwhile, the pace of hiring pharmacists into Uganda’s public sector is too slow. Low socio-economic status of family in childhood (χ2 =2.77, p=0.10), admission through matriculation and diploma scheme (χ2 =2.37, p=0.12), internship in countryside hospitals (χ2 =2.24, p=0. 13), working experience before pharmacy school (χ2 =2.21, p=0.14), salary expectation (χ2 =1.76, p=0.18), and rural secondary education (χ2 =1.75, p=0.19) favored attraction but in a statistically insignificant manner. Retention was most favored by zero postgraduate qualification (χ2 =4.39, p=0.04), matriculation and diploma admission scheme (χ2 =2.57, p=0.11), and working experience in private sector (χ2 =2.21, p=0.14). Conclusions: The pace of hiring of pharmacists into Uganda’s public health sector is too slow and should be stepped up. Besides work incentives, affirmative action to increase admissions into pharmacy degree training programs through matriculation and diploma schemes and for children with rural childhoods should be considered.
Keywords: Uganda; Public hospital pharmacist; Attraction; Retention; Human resources for health